Light harvesting complexes of Chromera velia, photosynthetic relative of apicomplexan parasites - Tichy, Josef; Gardian, Zdenko; Bina, David; Konik, Peter; Litvin, Radek; Herbstova, Miroslava; Pain, Arnab; Vacha, Frantisek (Biochimica et biophysica acta, 2013)
The structure and composition of the light harvesting complexes from the unicellular alga Chromera velia were studied by means of optical spectroscopy, biochemical and electron microscopy methods. Two different types of antennae systems were identified. One exhibited a molecular weight (18-19kDa) similar to FCP (fucoxanthin chlorophyll protein) complexes from diatoms, however, single particle analysis and circular dichroism spectroscopy indicated similarity of this structure to the recently characterized XLH antenna of xanthophytes. In light of these data we denote this antenna complex CLH, for "Chromera Light Harvesting" complex. The other system was identified as the photosystem I with bound Light Harvesting Complexes (PSI-LHCr) related to the red algae LHCI antennae. The result of this study is the finding that C. velia, when grown in natural light conditions, possesses light harvesting antennae typically found in two different, evolutionary distant, groups of photosynthetic organisms.
Keywords: Photosystem I Protein Complex; proteiny vázající chlorofyl; světlosběrné proteinové komplexy; cirkulární dichroismus; fotosystém I (proteinový komplex); Alveolata; Light-Harvesting Protein Complexes; Circular Dichroism; Photosynthesis; fotosyntéza; Chlorophyll Binding Proteins